Kuntowijoyoâ€™s Prophetic Social Science (Chalenges and Consequences) - Luqman Rico Khashogi (Ijtimā`iyya: Journal of Muslim Society Research, 2017)
The dynamics of social science in Indonesia today is likely looking for the ideal form. Kuntowijoyo, in this case, becomes one of the Indonesian Muslim figures who brings fresh air for the social sciences by integrating Islamic paradigm that is transcendental/divine (prophetic). The working device is expected to be applicable in the future in order to look at the social dynamics of the Muslims; its culture, its history of the social and political movements. Thus, the purpose of this study was to see the importance of the Islamic paradigm in the social sciences and also to assure that the application of the scientific framework (that is called by Kuntowijoyo) Prophetic Social Sciences should be started as soon as possible. Therefore, this study is descriptive-comparative. Kuntowijoyo ideas provide a comparison among the opinions of other social scientists to see the relevance of his thoughts within the dynamics of value-laden social science. This study presents that the social observation of the Muslim society so far is not only always value-laden, but also full of certain messages and also unwittingly spread the used paradigm, it is not only pure interpretation. Thus, the working device of developing social science today does not only need critical examination, but also need to be improved to scrape a variety of Muslim social problems; culture, history, social movements, and political. The prophetic values require provocative motion (da'wah), professionalism (jihad), and strong integrity (amanah).